GLOBALIZATION CHALLENGES IN CENTRAL ASIA AND CERTAIN ASPECTS OF CHINA’S CENTRAL ASIAN POLICIES - IMANALIEV, Muratbek; ABDYLDAEV, Erlan (CENTRAL ASIA AND THE CAUCASUS, 2007)
Recently countries and continents have become aware, to different degrees, of common globalization problems. More than that: political and academic communities of various parties, academic schools, and trends have been busying themselves with investigations into the nature of these problems. This explains the variety of approaches to the current globalization problems. The too complex and too ambiguous processes permit convincing arguments in favor of widely diverse approaches. At the same time, when talking about globalization and its impact on specific countries and regions (in the developing world in particular), it is wise to discuss it in the context of two key trends: the world’s increasingly universal nature and its growing diversity. Their interaction and confrontation determine the world’s development, its highly ambiguous nature and, most important, the alternatives for each nation and each state.1It looks as though, in the last decades of the 20th century, mankind reconciled itself to the inevitable—immersion into globalization, its positive and negative sides notwithstanding. The forecasts of the development vectors of world civilization are as varied as ever. This is also determined by the fact that any country or group of countries that offers mankind a conception or vision of the future claims a privileged position for itself over others in an effort to protect its future interests. The futu rologists and political scientists agree that all spheres of human and state activities will undergo radical changes. This is true, first and foremost, of politics, the economy, culture, the environment, and the relations between countries, regions, religions, races, etc. On the other hand, we have to admit that globalization (particularly its international political aspect) requires tighter control and regulation on an increasingly wider scale. In fact, this is developing into an imperative. Globalization of science, technology, and communication in the crowded world with its highly concentrated capital and economy and against the background of potentially destructive ecological processes and military might demands that the risks of further evolution of world economy and international relations be reduced to the minimum.